The Women Empowerment from Fishermen Family Based on Social and Economic Character for Independent Entrepreneurs - Hidayanur, Hidayanur; Dian Wisika Prajanti, Sucihatiningsih; Rodiyah, Rodiyah (Universitas Negeri Semarang, 2019)
A strategic development program that is a global concern is the achievement of sustainable development goals. The goal of sustainable development has 17 achievement targets, one of which is gender equality and empowerment. The purpose of this study was to analyze the empowerment of women of character-based fishing families in Kedawung Village, Banyuputih District, Batang Regency. A qualitative approach, type of social descriptive research, primary, secondary and tertiary data sources. Data collection techniques are observation, interviews, and documentation. Data validity uses triangulation. The results showed that the characteristics of women in fishermen families in Kedawung Village were social and economic independence in entrepreneurship. Women's empowerment has been effective in the Fishermen Village, supported by the Department of Maritime Affairs and Fisheries in the form of entrepreneurial processed fishers, as well as providing a sales platform in a particular market for fishers. The benefits of this research are expected to provide information on what can be done in effective empowerment for women in fishing families in the fields and forms of empowering women in fishermen’s families.